Pregnancy in adolescence in Brazil: associated factors with maternal age - Thamara de Souza Campos Assis; Katrini Guidolini Martinelli; Silvana Granado Nogueira da Gama; Edson Theodoro dos Santos Neto (Instituto Materno Infantil de Pernambuco, 2022)
Abstract Objectives: describing maternal characteristics, risk behavior, obstetric data, prenatal care and childbirth in adolescent mothers in Brazil (age groups: 12-16 years and 17-19 years). Methods: hospital-based cross-sectional study substantiated by Nascer no Brasil", (Born in Brazil) data. The study encompassed puerperal adolescent mothers from all regions in the country, and their newborns. Chi-square test was used to compare adolescents in the 12-16 years old age group and those in the 17-19 years old age group. Results: pregnant women in the 12-16 years old age group mostly lived in the Northeast of Brazil (p=0.014); most of them did not have a partner (p<0.001), unplanned pregnancy (p<0.001), they had inadequate schooling for their age (p=0.033), had less than six prenatal consultations (p=0.021), were subjected to episiotomy (p=0.042) and accounted for the largest number of premature babies (p=0.014). Conclusions: puerperal women in the 12-16 years old age group presented vulnerability in their socioeconomic conditions, inadequate assistance at the prenatal and childbirth care, as well as their babies showed neonatal complications that pointed towards these adolescent mothers' need of multidisciplinary care.